Community Blockchain Record-Keeping Method for Agricultural Land Leases using Design Science Research Approach - Loh, Yin Xia; Huspi, Sharin Hazlin; Amerhaider Nuar, Ahmad Najmi (JOIV : International Journal on Informatics Visualization, 2025)
In Malaysia, agricultural land lease records are still predominantly maintained on paper, making them vulnerable to loss, damage, and tampering. The study presents a novel, community-based blockchain record-keeping system designed explicitly for agricultural land leasing. Its primary objective is to enhance the transparency, trust, and efficiency of lease transactions between landowners and small-scale farmers. The system leverages Hyperledger Fabric in combination with the Interplanetary File System (IPFS) to ensure lease agreements are stored securely and immutably. By using decentralized storage, the documents remain accessible when needed while reducing the risk of unauthorized modifications. The design of this system is grounded in Work System Theory (WST), which emphasizes the integration of technology with the people, processes, and environmental factors involved in land leasing. To ensure the development approach aligns with the complexities of the real-world context, the study employs Situational Method Engineering (SME). This methodology involves selecting and tailoring components from existing methods to create a solution customized for agricultural land leasing. By combining a robust technical foundation with a design that accounts for community dynamics and legal considerations, the study demonstrates how blockchain can serve not only as a data management tool but also as a means of promoting fairness and transparency in rural land governance. The artefact marks a significant step toward building digital trust in the management and documentation of agricultural land.